Anti-Kelch-like protein 11 antibody encephalitis: a case report and literature review - Song, Yanling; Hu, Quanzhong; Zhang, Qing (Frontiers in Neurology, 2023)
Anti-Kelch-like protein 11 (KLHL11) antibody encephalitis is a rare clinical condition characterized by autoimmune-mediated encephalomyelitis associated with the presence of KLHL11 antibodies. Diagnosis requires the detection of serum and cerebrospinal fluid anti-KLHL11 antibodies, while immunotherapy serves as the principal treatment approach. This paper presents a case report highlighting the emergence of anti-KLHL11 antibody encephalitis. A 66-year-old male patient presented with seizures, impaired cognitive function, disturbance of consciousness, apathy, hypologia, dysphoria, and ataxia. Serum and cerebrospinal fluid (CSF) were identified as positive for anti-KLHL11 antibodies, leading to a diagnosis of autoimmune encephalitis associated with KLHL11 antibodies. After treatment with glucocorticoid, the patient did not experience further convulsions and recovered consciousness, with improved cognitive function. Tumor screening suggested the presence of an underlying malignancy. The clinical manifestations of anti-KLHL11 antibody encephalitis vary widely, and timely identification and treatment can improve prognosis.